Daniel T. Ellis papers - Ellis, Daniel T.
ALS (1865 February 24) from Ellis, a Union soldier stationed at a prison for Confederate soldiers at Rock Island, Ill., describing prison conditions.
Soldier in the Union Army.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Illinois -- History -- Civil War, 1861-1865.; Rock Island (Ill.) -- History; United States -- History -- Civil War, 1861-1865 -- Personal narratives; United States -- History -- Civil War, 1861-1865 -- Prisoners and prisons; Soldiers